(untitled) (The Educator Journal, 2025)
This study examines the influence of technology and social media in shaping the sports journeys and identity construction of young athletes in Nepal, focusing on the experiences of a female volleyball player from Barpak-Sulikot Rural Municipality, Gorkha, Nepal. A qualitative case study was employed, with data collected through in-depth interviews. The participant, a young female volleyball player, referee and student from a highly marginalized indigenous community of rural Nepal, was selected for her dual role as an athlete and referee, reflecting her remarkable achievements despite financial and socio-cultural challenges. Data were analyzed through coding and thematic exploration to derive insights into the intersection of sports, digitalization, and personal development. The study reveals two overarching themes: (1) the influence of limited technological resources and socio-cultural norms on athletic growth and digital engagement, and (2) the strategic use of social media platforms like TikTok and YouTube for personal branding, skill development, and professional connectivity. The findings expose how early exposure to digital tools, such as recorded gameplay and sports tutorials, fosters skill enhancement, confidence, and recognition. This study provides insight into how athletes in developing countries navigate the dual pressures of traditional socio-cultural expectations and modern digital demands.